The Inflammasome and Type-2 Immunity in Clostridium difficile Infection - Donlan, Alexandra; Petri, William A., Jr. (Clinics in Colon and Rectal Surgery, 2020)
Clostridium difficile (reclassified as “Clostridioides”) is the leading cause of hospital-acquired infections in the United States, and is associated with high-patient mortality and high rates of recurrence. Inflammasome priming and activation by the bacterial toxins, TcdA, TcdB, and C. difficile transferase (CDT), initiates a potent immune response that is characterized by interleukin- (IL) 8, IL-1β, and neutrophil recruitment, and is required for pathogen killing. However, it is becoming clearer that a strong inflammatory response during C. difficile infection can result in host tissue damage, and is associated with worse patient outcome. Recent work has begun to show that a type-2 immune response, most often associated with helminth infections, allergy, and asthma, may be protective during C. difficile infection. While the mechanisms through how this response protect are still unclear, there is evidence that it is mediated through eosinophil activity. This chapter will review the immune response to C. difficile, how the inflammasome signaling during infection can deleterious to the host, as well as the current understanding of a protective type-2 immunity. Understanding the host immune response may help to provide insight into novel approaches to prognosis markers, as well as how treat patient C. difficile infection without, or in addition to, antibiotics.
Keywords: Clostridium difficle; diarrhea; inflammasome; type-2 immunity